Immersive Experience in 3D Data Visualization with Virtual Reality - Yulistiawan, Bambang Saras; Krisnanik, Erly; Puspita Dewi, Catur Nugrahaeni; Pinastika, I Wayan Rangga (Journal of Intelligent Decision Support System (IDSS), 2025)
Immersive experiences in 3D data visualization using Virtual Reality (VR) technology are increasingly important in the digital era with an ever-increasing volume of data. VR allows users to interact with data in three dimensions to improve understanding and analysis of complex information. Research shows that interactions in VR environments can speed up the identification of patterns and anomalies, as well as increase user understanding of data by up to 30% compared to traditional methods. This research aims to provide an alternative to the use of immersive technology with VR to provide immersive data visualization. The development of 3D data visualization prototypes using Oculus, Meta Quest 2, and Unity is expected to be an interactive platform for users. Despite the challenges related to ergonomics and comfort, the potential for VR in improving communication and data understanding is enormous. Systematic VR development methods, through planning, design, development, testing, and maintenance steps, are essential to ensure the application is effective and meets the needs of users.